Revenir vers les habitants, revenir sur les territoires - Elizabeth Auclair (Développement Durable et Territoires)
Sustainable development was supposed to be a “civilization” concept, but the power of the economic interests and the pressure of the environmental issues have fragilized the concept. With the recent world crisis, many questions now arise: we must change our model, but how do we want to live, with which values and indicators, in what kind of towns and territories? In this article we propose to analyse how cultural development can help to reach the aim of “living together”. Indeed, taking into account cultural diversity and initiating local activities enables to develop new kinds of projects with the inhabitants, and to promote essential values such as local democracy, solidarity, tolerance, proximity… The changes in the French cultural policies seem to show that things are moving that way.